Noninvasive ventilation during the weaning process in chronically critically ill patients. Issue 4 (28th October 2016) - Sancho, Jesus; Servera, Emilio; Jara-Palomares, Luis; Barrot, Emilia; Sanchez-Oro-Gómez, Raquel; Gómez de Terreros, F. Javier; Martín-Vicente, M. Jesús; Utrabo, Isabel; Núñez, M. Belen; Binimelis, Alicia; Sala, Ernest; Zamora, Enrique; et al.
Chronically critically ill patients often undergo prolonged mechanical ventilation. The role of noninvasive ventilation (NIV) during weaning of these patients remains unclear. The aim of this study was to determine the value of NIV and whether a parameter can predict the need for NIV in chronically critically ill patients during the weaning process. We conducted a prospective study that included chronically critically ill patients admitted to Spanish respiratory care units. The weaning method used consisted of progressive periods of spontaneous breathing trials. Patients were transferred to NIV when it proved impossible to increase the duration of spontaneous breathing trials beyond 18 h. 231 chronically critically ill patients were included in the study. 198 (85.71%) patients achieved weaning success (mean weaning time 25.45±16.71 days), of whom 40 (21.4%) needed NIV during the weaning process. The variable which predicted the need for NIV was arterial carbon dioxide tension at respiratory care unit admission (OR 1.08 (95% CI 1.01–1.15), p=0.013), with a cut-off point of 45.5 mmHg (sensitivity 0.76, specificity 0.67, positive predictive value 0.76, negative predictive value 0.97). NIV is a useful tool during weaning in chronically critically ill patients. Hypercapnia despite mechanical ventilation at respiratory care unit admission is the main predictor of the need for NIV during weaning. NIV is a useful tool during weaning in chronic critically ill patients independent of their premorbid condition http://ow.ly/j4Av304sEoJ